Content and organization of sports training taijiquan for adults - Zhu Zehuan,; Baranov V.A. , (Theory and Practice of Physical Culture, 2025)
The content of adult Taijiquan sports training needs to be adjusted and a more accurate scientific approach to the organization of classes. It is important to take into account such important aspects that a significant part of those involved consider Taijiquan as a sport, engaging in this type of activity at least three times a week. Training sessions have their own specifics, determined to a greater extent by the correction and maintenance of one's body, as well as the psychosomatic regulation of the body.